Switched-currents an analogue technique for digital technology - Toumazou, C. (Chris); Hughes, J. B. (John B.); Battersby, N. C. (Nicholas C.) (P. Peregrinus on behalf of the Institution of Electrical Engineers, 1993)
The book reviews developments in the following fields: analogue technique; digital technology; switched-current; filters; and data converters.